2023
DOI: 10.2478/cjf-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

Length-Weight Relationship and Condition Factor of Seven Fish Species in Manasbal Lake, Kashmir, India

Abstract: For aquaculture assessments, the length-weight relationship and condition factor are considered as standard methods for determining fish growth, its health and the potential yield. A year-long study was conducted to calculate length-weight relationships (LWRs) and condition factor (K) for seven fish species, Schizothorax niger (Alghad or snowtrout), S. curvifrons (Sattar snowtrout), Cyprinus carpio (Common carp), Carassius carassius (Crucian carp), Pethia conchonius (Rosy barb), Crossocheilus diplochilus (Kash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
2
1
1
Order By: Relevance
“…The lake shows seasonal temperature induced stratification with anoxic bottom water, confirming previous findings (Yaseen, 2012; Yousuf, 1979). The interaction of the epilimnion with the atmosphere, coupled with an abundant production of oxygen from photosynthetic activity, yields elevated DO concentrations in the upper lake water surface.…”
Section: Discussionsupporting
confidence: 90%
“…The lake shows seasonal temperature induced stratification with anoxic bottom water, confirming previous findings (Yaseen, 2012; Yousuf, 1979). The interaction of the epilimnion with the atmosphere, coupled with an abundant production of oxygen from photosynthetic activity, yields elevated DO concentrations in the upper lake water surface.…”
Section: Discussionsupporting
confidence: 90%
“…A vital bioecological tool, Length-Weight Relationships (LWRs) provide crucial insights about biomass estimation, fish becoming slimmer as its length increases 4,22 . Similar reports of negative allometric growth have been reported by Sidiq et al, 23 Bhat et al, 11 Qazi et al, 21 and Yousuf et al, 24 in C. diplochilus. The association between LLRs was reported to be highly significant, with r 2 value of 0.98 for TL, SL and FL, which conforms with the findings of Qazi et al, 21 and Malhotra and Chauhan 25 .…”
Section: Discussionsupporting
confidence: 85%
“…As per the criterion set by Fulton 28 , the condition factor of C. diplochilus is reflective of the poor condition of fish within the lake. The condition factor reported during the current study was found to be lesser than the one reported by Bhat et al, 11 and Yousuf et al, 24 while working in Dal and Manasbal Lake respectively. The probable reasons for the same could be the use of a net with a bigger mesh size during both the studies and better habitat conditions of Manasbal Lake.…”
Section: Discussioncontrasting
confidence: 82%
“…In aquaculture, the condition factor (CF) is one criterion used to assess fish growth [39]. Although the CF cannot represent the overall growth performance of fish, in this study, M. oleifera and B. amyloliquefaciens supplementation significantly enhanced the VSI and GSI of Nile tilapia, and these two additions had an interaction with VSI and GSI.…”
Section: Discussionmentioning
confidence: 83%